FREEABLE EDUCATION (Efforts in Contruction the Goal of Characterized) - Syahran Jailani (PRIMARY EDUCATION JOURNAL (PEJ), 2019)
Abstract The education is an important instrument for human being in order to be free from foolery. The failure of the education system will affect the educational process faced by learners, the history has recorded in many countries; the involvement of a state in determining education policy did not focus on the learners, it will give birth the artificial generation and does not have quality. The education liberates and gives the learners the space is solutif offering in achieving educational excellence and intelligent character to be new Indonesia. Keyword: Freeable education, children characterized..